(untitled) (Altre Modernità, 2022)
The aim of this contribution is to investigate to what extent the sudden switch to distance learning and teaching in response to the Covid-19 pandemic impacted on the relation between the university system and the social fabric, in particular with respect to lifelong learning, a central component of the Third Mission. The starting point for the considerations which will be the carried out is the course for external users “German Language for Specific Purposes”, which was held in January and February 2021 at the University of Verona in the realm of the departmental Project of Excellence and the MultilinVR project. The outbreak of pandemic has made the educational role of university towards the different social actors even more significant, since they have been experiencing new goals and motivations, which have evolved and rephrased along with the modified social conditions. After having considered the educational needs of the participants, we will discuss the strategies which allowed for cooperative and situated learning – both in synchronous and asynchronous classes – and we will show how interaction was a deciding factor for this lifelong learning proposal to be effective. Moreover, the role and the forms of assessment will be analysed, as it assumes a function which is relevantly different from the objectives it pursues for canonical university students.